2010
DOI: 10.1309/ajcp0xqdgkfr0htw
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Flow Cytometric Antibody Panel for Distinguishing Burkitt Lymphoma From CD10+ Diffuse Large B-Cell Lymphoma

Abstract: Rapid and accurate differential diagnosis between Burkitt lymphoma (BL) and CD10+ diffuse large B-cell lymphoma (DLBCL) is imperative because their treatment differs. Recent studies have characterized several antigens differentially expressed in these 2 types of lymphoma. Our goal was to determine whether use of these markers would aid in the differential diagnosis of BL vs CD10+ DLBCL by flow cytometric immunophenotyping (FCI). Twenty-three cases of CD10+ B-cell lymphomas with available cryopreserved samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 29 publications
3
15
0
Order By: Relevance
“…For example, CD44 and CD54 expression was shown to be significantly different between these 2 lymphomas by Schniederjan et al 9 However, these markers are not commonly used in many clinical laboratories. Although no differences in the expression of CD18 or CD43 were observed in that study, BL showed brighter CD43 intensity than CD10+ DLBCL in our analysis ( P = .029).…”
Section: Discussionmentioning
confidence: 99%
“…For example, CD44 and CD54 expression was shown to be significantly different between these 2 lymphomas by Schniederjan et al 9 However, these markers are not commonly used in many clinical laboratories. Although no differences in the expression of CD18 or CD43 were observed in that study, BL showed brighter CD43 intensity than CD10+ DLBCL in our analysis ( P = .029).…”
Section: Discussionmentioning
confidence: 99%
“…showing superiority to conventional staining with CD10 and Bcl-2 [106], and combination of CD44 and CD54 [107].…”
Section: So Far Two Distinct Antibody Panels For Distinguishing Betwementioning
confidence: 96%
“…It functions as a lymphocyte homing receptor as well [17]. CD44 has many uses in histopathology, including as an epithelial marker, in the differentiation of some forms of lymphoma, and in evaluating early urothelial carcinomas [18,19]. Expression of CD44 has been studied in many different types of cancer, and the majority show loss of CD44 expression to be linked to a worse prognosis [20].…”
Section: Discussionmentioning
confidence: 99%
“…Both generally present as submucosal masses and are histologically similar to papillary proliferation of ductal-type epithelium inside a salivary duct [6]. Prior reports of immunohistochemistry (IHC) of oral ductal papillomas have found positivity to cytokeratin (CK) markers such as AE1/3, Cam5.2, CK7, 8,13,14,18, and 19 along with epithelial markers such as epithelial membrane antigen (EMA) and carcinoembryonic antigen (CEA) [7][8][9][10][11][12]. The lesions have very little to no potential for malignant transformation, and in most cases no recurrence is reported after simple excision [6].…”
Section: Introductionmentioning
confidence: 99%